2021
DOI: 10.1016/j.jlr.2021.100056
|View full text |Cite
|
Sign up to set email alerts
|

Lipid remodeling in response to methionine stress in MDA-MBA-468 triple-negative breast cancer cells

Abstract: Methionine (Met) is an essential amino acid and critical precursor to the cellular methyl donor S-adenosylmethionine. Unlike nontransformed cells, cancer cells have a unique metabolic requirement for Met and are unable to proliferate in growth media where Met is replaced with its metabolic precursor, homocysteine. This metabolic vulnerability is common among cancer cells regardless of tissue origin and is known as "methionine dependence", "methionine stress sensitivity", or the Hoffman effect. The response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Future studies will also use other methods to investigate epigenetic modifications of histones in cancer, such as ChIP (23). The overmethylation of H3K4me3 and H3K9me3 found in the 3 major types of sarcoma in the present study may be related to methionine addiction, a fundamental hallmark of cancer (24)(25)(26)(27)(28), termed the Hoffman effect (29)(30)(31). The over-methylation of these histone marks required excess methionine in the form of S-adenosylmethionine and may, at least in part, account for the excess methionine required by cancer cells and is a basis why methionine restriction with recombinant methioninase has been an effective therapy for sarcoma in all major types of sarcoma PDOX models (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 76%
“…Future studies will also use other methods to investigate epigenetic modifications of histones in cancer, such as ChIP (23). The overmethylation of H3K4me3 and H3K9me3 found in the 3 major types of sarcoma in the present study may be related to methionine addiction, a fundamental hallmark of cancer (24)(25)(26)(27)(28), termed the Hoffman effect (29)(30)(31). The over-methylation of these histone marks required excess methionine in the form of S-adenosylmethionine and may, at least in part, account for the excess methionine required by cancer cells and is a basis why methionine restriction with recombinant methioninase has been an effective therapy for sarcoma in all major types of sarcoma PDOX models (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 76%
“…The present study showed o-rMETase significantly inhibited growth of livermetastasis TNBC. o-rMETase is of particular importance as it targets the methionine addiction of cancer, which is a fundamental and general hallmark of cancer discovered by us (12)(13)(14)(15)(16)(17)(18)(19)(20) and which is termed the Hoffman effect (21)(22)(23). Future clinical studies will combine low-dose chemotherapy with o-rMETase for TNBC to overcome the recalcitrance of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, methionine (Met) is an essential amino acid required for cancer cells to grow under in vitro conditions and is also important in lipid biosynthesis due to the requirement for S-adenyl-methionine [77]. Borrego et al assessed the impact of Met stress (deprivation) on the cellular lipid composition of TNBC MDA-MB-468 cells and a Met stress insensitive derivative, MDA-MB-468res-R8, under control and Met-stress conditions [78]. There was a rapid and extensive decrease in lipid abundance, except for unsaturated TGs, in Met-dependent MDA-MB-468 cells that was not observed in Met-res cells, and there was an associated increase in cytoplasmic lipid droplets reflecting an overall increase in neutral storage lipids.…”
Section: Breast Cancer Lipid Signatures In Cell Lines and Tumorsmentioning
confidence: 99%
“…The second obstacle is the types of breast cancer models used in previous published work. The majority of lipidomic studies discussed in this review used either breast cancer cell lines [69,71,73,76,78,81] or primary tumor samples [83][84][85][86]. As highlighted in Table 1, there is a clear disparity between lipid analytes detected in 2D cell line monoculture versus patient tumor samples, with only several key overlapping lipid species.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%